The Rise and Decline of Operative Obstetrics or, the Joys of a Peripatetic Obstetrician (Res Medica, 2014)
I awoke and it was a dream. This has encouraged me to share with you the joys of a peripatetic obstetrician who spent more than 40 years practising obstetrics when obstetrics, particularly operative obstetrics, truly was an Art. Sadly this is no longer the case, although one could, if one had the necessary experience, still practise this kind of obstetrics in a developing country where the patient would bless you for having saved her child and for having preserved her from a feared Caesarean section. It is almost impossible to convey the sense of achievement, joy and wonder when, bathed in sweat, after a difficult rotational forceps or breach delivery, one stands gazing at a new creation and shares with the parents their varying emotions.